Discordant anti-müllerian hormone (AMH) and follicle stimulating hormone (FSH) among women undergoing in vitro fertilization (IVF): which one is the better predictor for live birth? - Wang, Shunping (J Ovarian Res, 2018)
BACKGROUND: This study sought to clarify the roles of Anti-müllerian hormone (AMH) and follicle stimulating hormone (FSH) in predicting live birth, especially in patients with discordant AMH and FSH. A large IVF data set provided by eIVF®, consisting of 13,964 cycles with AMH, FSH, age, BMI, and birth outcomes were evaluated. Patients were categorized into four groups: Good prognosis group (AMH ≥1 ng/ml; FSH < 10 mIU/ml), Poor prognosis group (AMH < 1 ng/ml; FSH ≥10 mIU/ml), Reassuring AMH group (AMH ≥1 ng/ml; FSH ≥10 mIU/ml), and Reassuring FSH group (AMH < 1 ng/ml; FSH < 10 mIU/ml). The interaction between AMH, FSH, and their impact on live birth rate among these four groups was evaluated using Generalized Additive Mixed Modeling (GAMM). RESULTS: Analysis revealed a nonlinear relationship of AMH and FSH with live birth rate among all ages. Among the four groups, the good prognosis group had the highest live birth rate while the poor prognosis group had the lowest live birth rate (29.3% vs 13.1%, p < 0.005). In the discordant groups, the live birth rate of the reassuring AMH group was significantly higher than the reassuring FSH group (22.8% vs 15.6%, p < 0.005). CONCLUSIONS: Although both FSH and AMH are widely use to assess the ovarian reserve in women undergoing evaluation for infertility, AMH appears to be superior to FSH among all age groups. This is particularly important for patients with discordant AMH and FSH where reassuring AMH is a better clinical predictor of cycle success. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1186/s13048-018-0430-z) contains supplementary material, which is available to authorized users.